Transforming Cybersecurity Infrastructure : A Multi-dimensional Approach to Risk, Culture, and Technological Integration - Arun Harikrishnan (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
The rapid acceleration of digital transformation has exposed critical limitations in traditional cybersecurity approaches, particularly in their reactive nature and disconnection from broader organizational strategies. This article critically examines current cybersecurity practices in IT infrastructure management, identifying significant gaps in the integration of security measures with business objectives, organizational culture, and emerging technologies. Through a mixed-method analysis of industry practices and empirical data from multiple case studies, The article proposes a comprehensive framework that transcends conventional security paradigms. The article introduces a proactive, risk-based approach that integrates cultural transformation, emerging technologies, and resilience building while fostering strategic partnerships across stakeholder groups. Initial implementation across various organizational contexts demonstrates significant improvements in security posture, incident response times, and overall business alignment. The findings contribute to both theoretical understanding and practical application of integrated cybersecurity management, offering valuable insights for practitioners and researchers in the field of IT security and organizational resilience. This article addresses a critical gap in current literature by providing a holistic approach that aligns cybersecurity initiatives with organizational transformation while considering human factors and technological evolution.